Avaliação da regeneração natural em uma floresta estacional semidecidual submontana no sul do estado do Espírito Santo - Barreto, Andrêssa Mota Rios (2016)
is aims of this study was evaluate the natural regeneration of the shrubby arboreous stratum in a fragment of Submontane Semideciduous forest in the southern state of Espírito Santo, and verify the interaction of vegetation with some environmental variables. The inventory of natural regeneration was developed in the Private Reserves of Natural Patrimony (RPPN) Cafundó in 12 subplots of 1 x 20 m, where three classes of size were delimited on natural regeneration. Individuals were classified according to environmental group and dispersion syndrome. Data analysis included calculations of floristic diversity, evenness, estimated density and frequency of species and floristic similarity between the subplots of natural regeneration and between them and the adult stratum. To evaluate the influence of all the environmental variables (characteristic chemical and physical soil, soil moisture, canopy cover percentage and slope and altitude of the terrain) on community natural regeneration, Correspondence Analysis Canônica- CCA was sampled 678 individuals belonging to 73 species and 24 botanical families. Among the 24 families sampled in this study, Euphorbiaceae was the most representative in abundance and species showing a greater number of individuals were Actinostemon estrellensis and Goniorrhachis marginata. The Sorensen Similarity between natural regeneration and adult tree stratum was only 29%. The most representative ecological groups were the initial and late secondary and secondary zoochory was the predominant dispersion syndrome among species, followed by autochory. The Shannon index (H') was 3.13 nats.ind- ¹ and evenness (J) was 0.72. The environmental variables that showed no redundancy in the CCA were carbon, phosphorus, Slope and canopy coverage, these explained the distribution of species in this fragment. Especially the kind Goniorrhachis marginata, Actinostemon estrellensis and Psychotria carthagenensis who had high correlation with these four environmental variables. Based on the above, it can be concluded that the RPPN Cafundó features a natural regeneration with high diversity and individual density when compared to studies carried out in the same vegetation type and that was little influence of environmental variables regarding the distribution of the regeneration of the species natural in RPPN Cafundó.